1971
DOI: 10.1104/pp.48.4.498
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Variation of Indole Glucosinolates in Woad (Isatis tinctoria L.)

Abstract: The exceptionally high levels in woad (Isatis tinctoria L.) of three indolic goitrogens, namely glucobrassicin, neoglucobrassicin, and glucobrassicin-l-sulfonate, permit the facile study of their distribution in the plant and their changes during its development. Woad seeds contain as much as 0.23 % fresh weight of glucobrassicin but no other indole glucosinolate, while 1-week-old seedlings also contain substantial amounts of neoglucobrassicin and glucobrassicin-l-sulfonate in their shoots whether grown in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
21
0
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 29 publications
(24 reference statements)
4
21
0
1
Order By: Relevance
“…Seed glucosinolates are rapidly metabolized during the onset of germination (Elliot and Stowe 1971;Bodnaryk and Palaniswamy 1990) including glucobrassicin, a major seed glucosinolate in A. thaliana (Petersen et al 2002). iv.…”
Section: Discussionmentioning
confidence: 99%
“…Seed glucosinolates are rapidly metabolized during the onset of germination (Elliot and Stowe 1971;Bodnaryk and Palaniswamy 1990) including glucobrassicin, a major seed glucosinolate in A. thaliana (Petersen et al 2002). iv.…”
Section: Discussionmentioning
confidence: 99%
“…The homologous, soluble enzyme was also the one studied earlier (28,29), and it may be the one responsible for the basic auxin supply of the growing plant. Nitrilase II parallels the abundance and distribution of glucosinolates in A. thaliana and other Brassicaceae (11,(36)(37)(38)(39), suggesting functional connections. The enzyme could be involved in furnishing auxin from glucosinolates during the early stages of seed germination and seedling growth (36).…”
mentioning
confidence: 87%
“…Nitrilase II parallels the abundance and distribution of glucosinolates in A. thaliana and other Brassicaceae (11,(36)(37)(38)(39), suggesting functional connections. The enzyme could be involved in furnishing auxin from glucosinolates during the early stages of seed germination and seedling growth (36).…”
mentioning
confidence: 87%
“…They showed that within the rhizosphere concentrations of 2‐PE ITC are sufficient to ‘select’ an active microbial population different from that of the bulk soil. This work has revived earlier studies which reported release of ITCs (Choesin & Boerner, 1991; Schreiner & Koide, 1993) or GSLs (Elliott & Stowe, 1971) from healthy, undamaged roots. Together, these findings raise questions of where GSLs are located in root systems, where and how their hydrolysis liberates ITCs into the rhizosphere of living roots, and what the links are to normal root developmental processes.…”
Section: Introductionmentioning
confidence: 99%